Synthesis of potential impurities of dabigatran etexilate. Issue 13 (3rd July 2017) - Reddy, U. Rajasekhar; Sreenivasulu, B.; Satheesh, D.; Sundaram, Dhanraj T. S. S.; Srikanth, G.; Douglas, S. Paul
ABSTRACT: The present work describes the origin, control, and synthesis of two potent impurities of dabigatran etexilate1, dabigatran dimer2, and dabigatran n -propyl ester3 from the commercially available raw materials 2-[(4-cyanophenyl)amino]acetic acid (4 ) and N -[3-amino-4-(methylamino)benzoyl]- N -2-pyridinyl-β -alanine ethyl ester (5 ). These impurities are the process-related impurities and may affect the quality of drug substance, during its manufacturing in large scale. These impurities are not only the crucial components in determining the quality and safety of the drug substance1 but also provide a better understanding of impurity profiling. GRAPHICAL ABSTRACT: